Prenatal diagnosis of 21 fetuses with balanced chromosomal abnormalities (BCAs) using whole-genome sequencing - Fu, Fang; Li, Ru; Dang, Xiao; Yu, Qiuxia; Xu, Ke; Gu, Weiyue; Wang, Dan; Yang, Xin; Pan, Min; Zhen, Li; Zhang, Yongling; Li, Fatao; et al. (Frontiers in Genetics, 2022)
Balanced chromosomal abnormalities (BCAs) are the most common chromosomal abnormalities and the frequency of congenital abnormalities is approximately twice as high in newborns with a de novo BCA, but a prenatal diagnosis based on BCAs is subject to evaluation. To detect translocation breakpoints and conduct a prenatal diagnosis, we performed whole-genome sequencing (WGS) in 21 subjects who were found BCAs, 19 balanced chromosome translocations and two inversions, in prenatal screening. In 16 BCAs on non-N-masked regions (non-NMRs), WGS detected 13 (81.2%, 13/16) BCAs, including all the inversions. All the breakpoints of 12 (12/14) cases of sufficient DNA were confirmed by Sanger sequencing. In 13 interrupted genes, CACNA1E (in case 12) and STARD7 (in case 17) are known causative and PDCL was found in subject (case 11) with situs inversus for the first time. Case 12 with abnormal ultrasound reached a definitive genetic diagnosis of CACNA1E-disease, while STARD7 exon deletion has never been found causative in patients. WGS provides the possibility of prenatal diagnosis in fetuses with BCAs, and its clinical significance also lies in providing data for postnatal diagnosis.